Achieving Accelerated And Shared Growth In Ghana : A MAMS-Based Analysis of Costs And Opportunities - Bogetić, Željko 1993- (The World Bank, 2008)
This paper relies on the recently developed Maquette for Millennium Development Goals Simulations (MAMS) model to assess the consistency of alternative scaling-up and policy packages for growth and achievement of the Millennium Development Goals in Ghana. In the baseline scenario, Ghana's strong near and medium-term growth outlook puts it in a good position to achieve the poverty Millennium Development Goal ahead of schedule, but other goals are likely to remain elusive before 2015. In the accelerated growth scenario-which addresses the major gaps in water and sanitation and other infrastructure-even more rapid growth and poverty reduction are possible, but important targets in the areas of education, health, and environment remain unattainable. Although growth is complementary to achievement of the Millennium Development Goals, the authors also find important growth-human development trade-offs in the near term. The estimates show that the resource requirements for achieving the key Millennium Development Goals by 2015 are large, reaching US